Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/14767058.2017.1336220
|View full text |Cite
|
Sign up to set email alerts
|

The first trimester combined test for aneuploidies – a single center experience

Abstract: Our results are similar to those of the main studies on the FMF method of first trimester screening for aneuploidies. Our numbers are small because of limited availability of the very specialized resources involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Our median maternal age was 31 years, which was comparable to other values registered in Spain (32.4 years in 2016) [23], Romania (29.6 years in 2017) [18,24] or in Poland (34 years in 2017) [19], for first-trimester screening population.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our median maternal age was 31 years, which was comparable to other values registered in Spain (32.4 years in 2016) [23], Romania (29.6 years in 2017) [18,24] or in Poland (34 years in 2017) [19], for first-trimester screening population.…”
Section: Discussionsupporting
confidence: 67%
“…Two other recent studies also reported similar detection rates [18,19] of 91.6% and 93.75%, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…The median CRL was 65.45 (range, 45.1–84) mm. In 97% of the patients, the racial origin was white; conception was spontaneous in 95% of the patients …”
Section: Resultsmentioning
confidence: 99%
“…Spina bifida is sometimes associated with genetic anomalies such as trisomy 18. Both major structural defects and common aneuploidies can be routinely diagnosed in the first trimester of pregnancy [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%